International Financial Market’s Integration and Modelling Returns of Risky Assets - Hassene, Ben Mbarek (Journal of Asian Business Strategy, 2011)
The aim of this paper is to test the ability of conditional and unconditional CAPM models to explain emerging markets returns in terms of their integration into the international market. We use data on 5 developed countries and 5 emerging countries as well as data on the Tunis Stock Exchange (TSE) after the reforms. The results show that the correlations between emerging markets returns and developed markets returns are very low and sometimes negative. Conditional APT (as well as conditional CAPM) has lower predictive power for emerging markets than for developed markets. Finally, following the financial reforms, Tunisian financial markets became more and more integrated to the international market (excess returns and unconditional beta consistent with predictions). However, conditional APT does not accurately explain Tunisian market returns. This study confirms the unavailability of an accurate modelling technique of the Tunis Stock Exchange structure.